Spread of kidney and liver pathology in cats in the city of Poltava - Deleichuk, O.; Kravchenko, S. (Scientific Progress & Innovations, 2025)
Diseases of the digestive and urinary systems in domestic cats occupy a significant part of non-contagious internal pathologies. Liver diseases in animals of this species are closely connected with kidney diseases. The results of scientific researches on the spread of liver and kidney pathology in domestic cats in the city of Poltava, conducted during 2021–2024 are presented in the article, which contains the information on the analysis of the structure of morbidity, the chronology of diseases during each year, as well as the age of diseased animals. The aim of the study was to analyze the clinical manifestations, laboratory indicators, and ultrasonographic signs of the hepatobiliary system pathology in cats, taking into account the signs of functional upsetting and/or ultrasonographic visualization of the kidneys.The information was systematized, considering the chronological and nosological structure of morbidity and age dynamics. The results of the study of 1,428 cats aged from one to 11 years with clinical, laboratory, or ultrasonographic signs of liver and kidney pathology were analyzed. It was found that liver pathology in cats in Poltava is accompanied by renal dysfunction on the average of 36 % of cases, among which 70.4 % are patients with acute cholangiohepatitis, 14 % are patients with chronic hepatitis, and 15.6 % with hepatodystrophy. It was established that in 2021, the number of cases of combined liver and kidney pathology in cats made 21 %, in 2022 – 23.2 %, in 2023 – 24.9 %, in 2024 – 30.9 %, which was associated with changes in the conditions of feeding and keeping domestic cats at the background of migration trends, accompanied by the violation of ensuring the physiological needs of animals and, accordingly, the development of metabolic diseases. The age dynamics of liver and kidney pathology are shown: acute inflammatory diseases prevail in young animals, chronic inflammatory processes were found in the nosological structure of animals aged 3-5 years, and dystrophic diseases of the hepatobiliary system and kidneys were found in cats of the older age group. It has been revealed that the predominant liver pathology accompanied by nephropathy is acute cholangiohepatitis at the age of 3-5 years (59.4 %), chronic hepatitis at the age of 6-8 years (44.4 %), and hepatodystrophy at the age of over 9 years (46.3 %).